Pengaruh Loyalitas Konsumen Terhadap Minat Pembelian Ulang Pada Produk Winmilk di Kota Cimahi, Indonesia - Amin, Lisana Sidqin Alya (Asosiasi Ahli Administrasi Indonesia, 2023)
This research article was prepared with the aim of finding out and analyzing the effect of consumer loyalty to make repeat purchases on Winmilk Products in Cimahi. The research method used is descriptive quantitative. The population in this study were all consumers of HIMAJAS. Data collection techniques were carried out by distributing questionnaires (gform) to 110 respondents. The analytical method used is Validity and Reliability Test, Normality, Simple Regression, and Hypothesis Testing. The results showed that consumer loyalty had a positive effect on consumer repurchase interest in Winmilk food products in Cimahi City. Consumer loyalty contributes 61% to consumer repurchase interest from this research.